Chapter Rereading Italian Travellers to Africa: Precursors, Identities and Interracial Relations in Narratives of Italian Colonialism - De Donno, Fabrizio (Connessioni. Studies in Transcultural History, 2022)
This essay considers a number of travellers' writings about Africa which are reread to construct and deconstruct Italian colonial identity. It focuses on Cesare Cesari's Viaggi africani di Pellegrino Matteucci (1932), which deems Matteucci a precursor of Fascist colonialism and contributor to Fascist "colonial science". The essay then moves on to explore the more recent rereading by Angelo Del Boca and Igiaba Scego of respectively Indro Montanelli's XX Battaglione Eritreo (1936) and Errico Emanuelli's Settimana nera (1961). By bringing together and rereading these texts, the essay maps the transformations of Italianness from colonial to postcolonial times and reveals how colonial identity relied on a series of gender, racial and sexual tropes of exploration and conquest.